2019
DOI: 10.3390/ijms20194725
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics of Salt-Tolerant and Salt-Sensitive Maize Inbred Lines to Reveal the Molecular Mechanism of Salt Tolerance

Abstract: Salt stress is one of the key abiotic stresses that causes great loss of yield and serious decrease in quality in maize (Zea mays L.). Therefore, it is very important to reveal the molecular mechanism of salt tolerance in maize. To acknowledge the molecular mechanisms underlying maize salt tolerance, two maize inbred lines, including salt-tolerant 8723 and salt-sensitive P138, were used in this study. Comparative proteomics of seedling roots from two maize inbred lines under 180 mM salt stress for 10 days were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 93 publications
(94 reference statements)
2
24
0
Order By: Relevance
“…Genes and proteins involved in plant hormone signal transduction and phenylpropanoid biosynthesis showed a positive correlation in salt response. Similar to previous studies [53,59,60], the metabolic pathways of plant hormone signal transduction, carotenoid biosynthesis, flavonoid biosynthesis, and starch and sucrose metabolism were involved in salt stress.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Genes and proteins involved in plant hormone signal transduction and phenylpropanoid biosynthesis showed a positive correlation in salt response. Similar to previous studies [53,59,60], the metabolic pathways of plant hormone signal transduction, carotenoid biosynthesis, flavonoid biosynthesis, and starch and sucrose metabolism were involved in salt stress.…”
Section: Discussionsupporting
confidence: 85%
“…In the analysis of salt treatment to two varieties of Origanum majorana, the Tunisian O. majorana plants developed tolerance to salinity by improved the process of galactosylation of quercetin into quercetin-3-galactoside and quercetin-3-rhamnoside [52]. Quantitative proteomic analyses of seedling roots from salt-sensitive and salt-tolerant maize were performed by using the iTRAQ method, phenylpropanoid biosynthesis, starch and sucrose metabolism, and the mitogen-activated protein kinase (MAPK) signaling pathway were enriched in salt-tolerant maize while only the nitrogen metabolism pathway was enriched in salt-sensitive maize [53]. Taken together, we found that synthesis and degradation of amino acids, ROS response, carbon metabolism and phenylpropanoid biosynthesis were highly related to salt response.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with previous studies of other plants: 150 DEGs were found be involved in regulating the level of ROS in Arabidopsis (Mittler et al, 2004) and NaCl treatment induced transcription of 75 ROS network genes in the roots of Arabidopsis (Jiang & Deyholos, 2006). Moreover, our study is also consistent with comparative proteomics studies on non-model plants (e.g., Casuarina glauca and Zea mays L.), which revealed the importance of enhanced antioxidant status to resist salt stress (Chen et al, 2019;Graca et al, 2019).…”
Section: Differential Gene Expressionsupporting
confidence: 92%
“…But those studies were mainly focused on Arabidopsis thaliana , Nicotiana tabacum , Oryza sativa , and other model plants (Dani et al 2005; Jiang et al 2007; Lakra et al 2019; Manaa et al 2011; Ndimba et al 2005; Sobhanian et al 2010; Zörb et al 2010), and some halophytic species, such as Suaeda salsa , Mesembryanthemum crystallinum , Haloxylon salicornicum , Puccinellia tenuiflora , and Porteresia coarctata (Barkla et al 2009; Li et al 2011; Panda et al 2020; Sengupta & Majumder 2009; Yu et al 2011). Proteomics approach has also been exploited to identify the key salt‐tolerance proteins by comparing the related plant species or contrasting genotypes under salinity, such as Arabidopsis thaliana/Thellungiella halophila , Triticum aestivum/Thinopyrum ponticum , Oryza sativa , Hordeum vulgare , Zea mays , and recently in Morus alba (Chen et al 2019; Damaris et al 2016; Gan et al 2021; Hussain et al 2019; Lakra et al 2018, 2019; Luo et al 2018; Pang et al 2010; Wang et al 2008; Witzel et al 2010). However, in case of millets, only a single study reported salt‐specific proteome responses, i.e.…”
Section: Discussionmentioning
confidence: 99%